School Principals' Support for Teachers' Professional Development in Indonesia and Japan - Widiyan, Agung Purwa; Takayoshi, Maki (Jurnal Akuntabilitas Manajemen Pendidikan, 2024)
This study aims to identify the role of school principals in supporting professional development (PD) programs in Indonesia and Japan. The method used is a literature review that collects and analyzes secondary data related to policies, programs, and practices of school principals in teacher professional development in both countries. The findings indicate that in Japan, school principals play a crucial role in facilitating PD through continuous leadership training and collaboration among teachers, while in Indonesia, although there are principal development programs, the focus is more on administrative skills and less on addressing real-world challenges in schools. This study suggests that Indonesia should adopt a more holistic approach to school leadership and teacher PD, strengthening the role of school principals in supporting and guiding PD, and introducing a more sustainable PD model that is integrated with daily teaching practices. Therefore, a coordinated effort between leadership development, teacher PD, and school community involvement is needed to enhance the quality of learning and education in Indonesia.